Shesher and Welala Floodplain Wetlands (Lake Tana, Ethiopia): Are They Important Breeding Habitats for Clarias gariepinus and the Migratory Labeobarbus Fish Species? - Wassie Anteneh; Eshete Dejen; Abebe Getahun (The Scientific World Journal)
This study aims at investigating the spawning migration of the endemic Labeobarbus species and C. gariepinus from Lake Tana, through Ribb River, to Welala and Shesher wetlands. The study was conducted during peak spawning months (July to October, 2010). Fish were collected through overnight gillnet settings. A total of 1725 specimens of the genus Labeobarbus (13 species) and 506 specimens of C. gariepinus were collected. Six species of Labeobarbus formed prespawning aggregation at Ribb River mouth. However, no Labeobarbus species was found to spawn in the two wetlands. More than 90% of the catch in Welala and Shesher wetlands was contributed by C. gariepinus. This implies that these wetlands are ideal spawning and nursery habitats for C. gariepinus but not for the endemic Labeobarbus species. Except L. intermedius, all the six Labeobarbus species (aggregated at Ribb River mouth) and C. gariepinus (spawning at Shesher and Welala wetlands) were temporally segregated.